North-South University Research Partnerships in Latin America and the Caribbean (International and Development Education, 2018)
This volume examines research productivity within schools in Latin America and the Caribbean (LAC) and presents examples of various successful LAC North-South programs which have propelled university research in the region. Much of the scholarly work on North-South research to date has concentrated principally on joint publications and co-authorship bibliometrics. In this book, cases are explored within the context of study on international research collaborations to highlight the motivations, mechanics, limitations, and success factors involved in the North-South relationships and their resulting research output.